2011
DOI: 10.1007/978-3-642-24449-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Performance Expectations and Guidelines for MPI Derived Datatypes

Abstract: Abstract. MPI's derived datatypes provide a powerful mechanism for concisely describing arbitrary, noncontiguous layouts of user data for use in MPI communication. This paper formulates self-consistent performance guidelines for derived datatypes. Such guidelines make performance expectations for derived datatypes explicit and suggest relevant optimizations to MPI implementers. We also identify self-consistent guidelines that are too strict to enforce, because they entail NP-hard optimization problems. Enforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Since some MPI implementations struggle to fulfill elementary performance expectations when handling derived datatypes [6], their adoption is not widespread yet. More and more success stories about improving performance using MPI DDTs are reported [1,8] and tools are available that enable users to quickly change their code from using manual pack loops to leveraging derived datatypes [10].…”
Section: Related Workmentioning
confidence: 99%
“…Since some MPI implementations struggle to fulfill elementary performance expectations when handling derived datatypes [6], their adoption is not widespread yet. More and more success stories about improving performance using MPI DDTs are reported [1,8] and tools are available that enable users to quickly change their code from using manual pack loops to leveraging derived datatypes [10].…”
Section: Related Workmentioning
confidence: 99%
“…One effort looked at exporting the MPI datatype capabilities to other programming systems [23]. In collaboration with other researchers, we examined the implications of adding performance requirements on MPI implementations for the use of datatypes in [14]; this is important in ensuring that users of MPI can count on reasonable behavior from their MPI implementations. Following up on this work, we have begun developing datatype optimization approaches that extend "just in time" compilation techniques to MPICH.…”
Section: Some Of the Most Interesting Results From This Project Addrementioning
confidence: 99%
“…However, performance of current datatype implementations remains suboptimal and has not received as much attention as latency and bandwidth, probably due to the lack of a reasonable and simple benchmark. For example Gropp et al found that several basic performance expectations are violated by MPI implementations in use today [9].…”
Section: Related Workmentioning
confidence: 99%
“…Not many scientific codes leverage MPI DDTs, even though their usage would be appropriate in many cases. One of the reasons might be that current MPI implementations in some cases still fail to deliver the expected performance, as shown by Gropp et al in [9], even though a lot of work is done on improving DDT implementations [6,18,20]. Most of this work is guided by a small number of micro-benchmarks.…”
Section: Introductionmentioning
confidence: 99%